Optimizing the Role of Ethics Ambassadors on Nurses' Ethical Behavior in Nursing Services - Irawan, Muhammad Henrie; Indryani, Betty; Iftiah , Nia (Open Access Health Scientific Journal, 2024)
Background: In nursing, ethical principles and discipline are very important. The role of ethical principles and discipline in determining how nurses behave ethically when they provide care . The application of good ethical behavior can improve the quality of nursing services, relationships with colleagues can be established good cooperation so that mutual interests can be fulfilled.Methods: The research method used in this study used case studies with a total sample.Results: the majority of ethics ambassadors perceive, have good concern for ethical and disciplinary issues as many as 8 (52.7%) respondents, with the majority of ethics ambassadors perceiving, have moderate difficulties in implementing ethics as many as 6 (46.1%) respondents. The majority of ethics ambassadors perceived, made very good consideration of ethical issues as many as 6 (46.1%) respondents.Conclusion: the implementation of ethical behavior of ethical ambassadors on ethical issues, can be categorized as well carried out at Hospital X East Kalimantan